2020
DOI: 10.1155/2020/8706283
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Minimally Invasive Techniques in the Treatment of Patellar Tendinopathy: A Systematic Review and Meta‐Analysis of Randomized Controlled Trials

Abstract: The aim was to determine the effectiveness of minimally invasive techniques (MIT) in patients with patellar tendinopathy. Database searches were performed for randomized controlled trials (RCTs) in electronic databases (WOS, Cochrane Central, SportDiscus, and Medline via PubMed and PEDro). The inclusion criteria used were published in English or Spanish and involving adults with patellar tendinopathy (pain on the inferior pole of the patella for a minimum of 3 months), with at least one group receiving MIT. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Looking at a general overview of our results, we found that EP is effective in the management of musculoskeletal disorders, which is consistent with the conclusions of the meta-analysis conducted by Gómez-Chiguano et al (17) and other qualitative systematic reviews (18,19,39,40). These articles reflected that one limitation of the scientific evidence concerning PE is the high variability in the parameters of application of the galvanic current.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Looking at a general overview of our results, we found that EP is effective in the management of musculoskeletal disorders, which is consistent with the conclusions of the meta-analysis conducted by Gómez-Chiguano et al (17) and other qualitative systematic reviews (18,19,39,40). These articles reflected that one limitation of the scientific evidence concerning PE is the high variability in the parameters of application of the galvanic current.…”
Section: Discussionsupporting
confidence: 91%
“…The result of these works is the first meta-analysis concerning the effects of PE on pain intensity and disability related to musculoskeletal pain where it is concluded that there is moderate evidence suggesting a large positive effect of PE to reduce pain and moderate evidence of a large decrease in pain-related disability for musculoskeletal pain conditions in the short, medium, and long term (15). However, like other reviews, they add that it is necessary to study the doses to unify more precise criteria for the application of PE and thus be able to reach a consensus on which clinical entities may be the most benefited by this type of therapy (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, this research also presents different strengths: this is the systematic review on percutaneous electrolysis in the treatment of tendinopathies that has analyzed the most studies to date. [41][42][43][44] In conclusion, the percutaneous electrolysis is effective for the treatment of tendinopathies showing results both immediately after the interventions analyzed and in those with long-term follow-up. The combination of this technique with eccentric training has proven to be one of the most effective treatments to improve tendinopathy pain to date.…”
Section: Discussionmentioning
confidence: 99%
“…The necrotic area of the tendon is debrided, and a rongeur is used to decorticate the distal pole of the patella to arrive at fresh bone. Moreover, multiple microperforations of the distal pole are made with a 2.5 mm k-wire to enhance the healing potential of the tendon attachment after debridement 6 . A PRP coat is placed under the tendon to stimulate further healing and a larger growth factor response (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Following the canonical classification of Blazina 5 , early symptomatic PT (Phases I and II) is often treated conservatively, such treatment including oral medications (non-steroidal anti-inflammatory drugs and corticosteroids), rest, immobilization, physical therapy (cryotherapy, extracorporeal shockwave therapy, ESWT) and eccentric exercise therapy 3 . New minimally invasive (MIT) topical techniques, such as platelet-rich-plasma (PRP) infiltrations or ultrasound-guided dry needling, are reserved for recalcitrant cases 6 . However, conservative treatment modalities aimed at modulating inflammation have had limited success in treating severe PT and also do not prevent painful conditions arising from overuse of tendons.…”
Section: Introductionmentioning
confidence: 99%